Socio-economic Determinants of Productivity in Tomato Farming: A Case Study of Gender Dynamics, Age, Education, Household Characteristics, and Land Ownership in Berekum West and Tano North Districts, Ghana - Anokye-Alexander, Danson; Adjei, Eric; Poku, Isaac Adu; Kennedy, Kontor; Debrah, Shadrack; Mensah, Frimpong Enock; Patrick, Ayensu; Prince, Adom; Hinneh, Sylvia Kyeremaa (Discoveries in Agriculture and Food Sciences, 2025)
Tomato farming is a vital component of the global agricultural sector, serving as a staple food and economic driver. This study examines the socio-economic characteristics of tomato farmers in Ghana, focusing on aspects such as gender, age, education, household size, and land ownership, to understand their impact on farming practices and productivity. The research was conducted in the Ahafo and Bono regions of Ghana using structured questionnaires and interviews with tomato farmers. The study reveals that the tomato farming sector is male-dominated, with a significant proportion of farmers being over 35 years old. Most farmers have basic education, small household sizes, and rent their farming lands. The majority do not have bank accounts or registered farm businesses. Agro-input dealers are the primary source of seeds and agrochemicals for farmers. Local tomato varieties are more commonly cultivated than improved varieties. Farmers’ choice of tomato variety is influenced by yield capacity, ease of cultivation, and market demand. Small farm sizes and low yields characterise tomato farming in the study area, which has limited income and production capacity. Farmers are generally aware of the dangers of pesticide use but lack access to protective clothing. Verbal communication from buyers is the primary source of market information. The study’s findings suggest that there must be targeted interventions to support tomato farmers, boost productivity, and encourage sustainable agricultural practices.